2011
DOI: 10.1371/journal.pone.0024705
|View full text |Cite
|
Sign up to set email alerts
|

Timing Is Critical for an Effective Anti-Metastatic Immunotherapy: The Decisive Role of IFNγ/STAT1-Mediated Activation of Autophagy

Abstract: BackgroundImmunotherapy is often recommended as an adjuvant treatment to reduce the chance of cancer recurrence or metastasis. Interestingly, timing is very important for a successful immunotherapy against metastasis, although the precise mechanism is still unknown.Methods and FindingsUsing a mouse model of melanoma metastasis induced by intravenous injection of B16-F10 cells, we investigated the mechanism responsible for the diverse efficacy of the prophylactic or therapeutic TLR4 and TLR9 agonist complex aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 43 publications
1
34
1
Order By: Relevance
“…The numbers of metastatic nodules in the lung was counted (top right), and the tumor volume in lung was calculated from the histographs using the formula (length  width 2 )/2 (bottom right). (43). We showed that knockdown of STAT1, but not STAT3 ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The numbers of metastatic nodules in the lung was counted (top right), and the tumor volume in lung was calculated from the histographs using the formula (length  width 2 )/2 (bottom right). (43). We showed that knockdown of STAT1, but not STAT3 ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 83%
“…STAT1 is an important downstream target of OSM-dependent pathways. Activation of STAT1 has been reported to be critical for the efficacy of anti-metastatic immunotherapies (43). The anticancer effect of OSM against chondrosarcoma is thought to work through the JAK3/STAT1 pathway (27).…”
Section: Oncostatin M Mediated the Msc-dependent Inhibition Of Cell Pmentioning
confidence: 99%
“…Treatment with TLR2-neutralizing antibody plus CpG ODN enhances the antitumor immunity and reduces immune suppression in the tumor microenvironment To find whether the differential immune responses induced by A number of studies indicate that IFN-γ can induce antitumor activity through STAT1 activation and autophagy induction [14,18,19] . By contrast, TGF-β1, IDO and COX2 are immunosuppressive factors that can promote tumor progression through the activation of Treg cells and suppression of T cell proliferation and responses [20] .…”
Section: Resultsmentioning
confidence: 99%
“…However, the combination regimen does not suppress tumor growth. This result may be due to the following: 1) the importance of TLR2 and TLR9 on host immune cells and tumor cells for positively modulating metastatic behavior compared to their minimal influence on primary subcutaneously implanted tumor growth [12,13,21,22] ; 2) the failure of the combination regimen to promote sufficient immune cell infiltration into the primary tumor to produce a potent cytotoxic suppression of tumor growth due to the anatomical site of administration [23] ; 3) the inability of the therapeutic administration of the combination regimen to overcome the immunosuppressive barrier after the suitable microenvironment for tumor growth has been established [14] . The TLR9 agonist CpG ODN is a promising anti-cancer immunotherapy based on its ability to safely stimulate Th1-dominant innate and adaptive immunity in humans [7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation